Sustained remission from depressive-like behavior depends on hippocampal neurogenesis - Pinheiro, António Mateus (2013)
Impairment of hippocampal neurogenesis has been associated with the expression of depressive-like symptoms and some studies have suggested neurogenesis as a critical factor in the normalization of behavior by antidepressant (AD) drugs. This study provides robust evidence that ongoing neurogenesis is essential for the maintenance of behavioral homeostasis and that its pharmacological arrest precipitates symptoms commonly found in depressed patients. Further, the incorporation of newly born neurons and astrocytes into the preexisting hippocampal neurocircuitry is shown to be necessary for the spontaneous recovery from the adverse effects of stress and for long-term benefits of AD treatments.